ENT 530 Social Media Portfolio: Happizza / Muhammad Zulfadhli Syam Md Zuber - Md Zuber, Muhammad Zulfadhli Syam (2021)
This report aims to achieve the main objective of Happizza that to be the best homemade pizza in Kuala Lumpur. This homemade pizza is to our beloved customer with affordable price and luxurious taste of pizza. Our business was started officially on 6 June in 2021. According to the customer who have try the pizza, our product gives a very delicious taste and feels like buying from big pizza store but cheaper. This product is also like by many citizens due to the sum of Malaysia taste of pizza that different from the others. Hence, this product provides a good insight for the continuation of sale to our customers. Since early of its opening, Happizza have sold their product more than 50 pack of pizza with variety of flavour that order by customer according to their tastes. Because of increasing demand for our product result into a good profitable sale revenue to our business product. As a result, Happizza's homemade pizza is a good marketable product of choice that can be expanded into many different places as the business grows.